You name it?! - Hayn, Evelyn (My University, 2016)
Based on a social constructivist, pragmatic cognitive understanding of naming, the study investigates the discriminatory hegemonic presuppositions and perceptions that are interpellated with personal names in Germany and Sweden. The critical lens of Black Feminist, Postcolonial, Postmigrant, Critical Trans and Disability Studies is applied in order to deconstruct current and past hegemonic naming norms. By regarding the un/intelligibility of names as constituted by intersecting power relations, racism_genderism_ableism_migratism_ classism, the dispositive model helps to identify what personal names and naming practices are made un/thinkable. Accustoming is introduced as an analytic tool to understand how hegemonic knowledge on naming is acquired and internalized in a structuralist and essentializing way. The analysis of administrative and legislative discourses demonstrates how hegemonic naming norms have been historically and institutionally accustomed. That a personal name is not only determined by institutional but also by individual decision-making is illustrated on the example of the child’s well-being, a commonly used argument for name decisions at registry offices. The feel for language as another norm to justify de_perceived name discrimination is analyzed against the background of how sprachgefühl as an emotive concept interpellates nationalist images of the self and the Other. The final chapter addresses the consequences of discriminatory naming practices: the definition and denial of personhood. The study concludes with a collection of empowering interventions in discriminatory naming practices and recommendations for a contra_ discriminatory anti-structuralist perception of personal names. By employing a transdisciplinary approach, the study illustrates how disciplinary boundaries are transgressed and how different discourse areas and material that traditionally are investigated in law, history, linguistics and literature is integrated in Gender Studies research.

Ausgehend von einem sozialkonstruktivistischen, pragmatisch-kognitiven Verständnis von Namen untersucht die Studie die diskriminierenden Wahrnehmungen, die über Personen-namen in Deutschland und Schweden aufgerufen werden. Durch Anwendung der kritischen Theorien und Zugänge der Black Feminist, Postcolonial, Postmigrant, Trans und Disability Studies auf Namensdiskurse werden gegenwärtige sowie historische hegemoniale Normen dekonstruiert. Mit Hilfe des durch intersektionale Machtverhältnisse konstituierten Dispositivmodells wird die Intelligibilität von Personennamen zur Diskussion gestellt. Vergewohnheitung (accustoming) als neues analytisches Konzept macht nachvollziehbar, wie hegemoniales Wissen zu Namensgebung auf strukturalistische und essentialisierende Weise erworben und internalisiert wird. Die Analyse administrativer und legislativer Diskurse zeigt, wie hegemoniale Namensnormen historisch und institutionell vergewohnheitet wurden. Dass ein Personenname institutionell auch durch individuelle Wahrnehmung bestimmt wird, illustriert die Analyse des ‚Kindeswohl‘, einem zentralen Argument für Namensentscheidungen auf Standesämtern. Ein weiteres Beispiel für die Rechtfertigung ent_wahrgenommener diskriminierender Namenspraktiken ist das Sprachgefühlkonzept, dessen Verwendung daraufhin untersucht wird, inwiefern es nationalistische Vorstellungen des Eigenen und des Anderen aufruft. Schließlich wird die An- und Aberkennung von Menschsein als Konsequenz diskriminierender Namenshandlungen adressiert. Eine Sammlung empowernder Interventionen in diskriminierende Namenspraktiken sowie Empfehlungen für eine kontra_diskriminierende, antistrukturalistische Wahrnehmung von Personennamen runden die Studie ab. Mit ihrem transdisziplinären Ansatz veranschaulicht die Arbeit, wie disziplinäre Grenzen überschritten und Diskursfelder und -materialien, die traditionellerweise in den Rechts-, Geschichts-, Sprach- und Literaturwissenschaften analysiert werden, in die Genderforschung integriert werden können.
Everyday discrimination through accustomed perception of personal names
Keywords: Sprache; Diskriminierung; Hegemonie; Normen; Kinder; 401 Sprachphilosophie, Sprachtheorie; Name